Methionine Aminopeptidase 2 (MetAP2) Inhibitor BL6 Attenuates Inflammation in Cultured Microglia and in a Mouse Model of Alzheimer’s Disease - Xiuli Zhang; Shivakumar Subbanna; Colin R. O. Williams; Stefanie Canals-Baker; Audrey Hashim; Donald A. Wilson; Louis M. Weiss; Srushti Shukla; Parthiban Chokkalingam; Sasmita Das; Bhaskar C. Das; Mariko Saito (Molecules, 2025)
Methionine aminopeptidase 2 (MetAP2) plays an important role in the regulation of protein synthesis and post-translational processing. Preclinical/clinical applications of MetAP2 inhibitors for the treatment of various diseases have been explored because of their antiangiogenic, anticancer, antiobesity, antidiabetic, and immunosuppressive properties. However, the effects of MetAP2 inhibitors on CNS diseases are rarely examined despite the abundant presence of MetAP2 in the brain. Previously, we synthesized a novel boron-containing MetAP2 inhibitor, BL6, and found that it suppressed angiogenesis and adipogenesis yet improved glucose uptake. Here, we studied the anti-inflammatory effects of BL6 in SIM-A9 microglia and in a mouse model of Alzheimer’s disease generated by the intracerebroventricular (icv) injection of streptozotocin (STZ). We found that BL6 reduced proinflammatory molecules, such as nitric oxide, iNOS, IL-1β, and IL-6, together with phospho-Akt and phospho-NF-κB p65, which were elevated in lipopolysaccharide (LPS)-activated microglial SIM-A9 cells. However, the LPS-induced reduction in Arg-1 and CD206 was attenuated by BL6, suggesting that BL6 promotes microglial M1 to M2 polarization. BL6 also decreased glial activation along with a reduction in phospho-tau and an elevation in synaptophysin in the icv-STZ mouse model. Thus, our experiments demonstrate an anti-neuroinflammatory action of BL6, suggesting possible clinical applications of MetAP2 inhibitors for brain disorders in which neuroinflammation is involved.